Studies on antioxidant, hepatoprotective, and vasculoprotective potential of Viola odorata and Wrightia tinctoria. (17th June 2019) - Jamshed, Humaira; Siddiqi, Hasan Salman; Gilani, Anwar‐ul‐Hassan; Arslan, Jamshed; Qasim, Muhammad; Gul, Bilquees
Abstract : We have reported the antidyslipidemic, antihypertensive, and Ca ++ channel blocking activities of Viola odorata (VO) and Wrightia tinctoria (WT). This study extends our understanding of their therapeutic potential by exploring the effects on biomarkers of hepatic and vascular dysfunction together with phytochemical standardization and antioxidant potential. Total phenolic compounds, total flavonoids content, and proanthocyanins of the methanolic extracts were identified using HPLC. Antioxidant capacity was measured using the in vitro assays. Two studies of 6‐week duration were conducted on a high‐fat diet rat model to test the leaves and seed extracts of VO and WT (300 and 600 mg/kg) for their effect on biomarkers for hepatic and vascular dysfunction. The HPLC analysis showed high contents of total phenolic compounds, total flavonoids content, and proanthocyanins along with distinctive phenolic composition. Both extracts exhibited significant antioxidant potential in 1, 1‐diphenyl‐2‐picrylhydrazyl, 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid), fluorescence recovery after photobleaching, and total antioxidant capacity (TAC) assays, comparable with synthetic standard antioxidants. The in vivo studies indicated a significant reduction in the high‐fat‐diet‐induced rise in serum uric acid, phosphorus, aspartate aminotransferase, alanine aminotransferase, and gamma‐glutamyl transferase. This study indicates the potential of VO and WT to protect from vascular and hepatic damage and an antioxidant effect, thus making these herbs strong candidates for managing cardiometabolic disorders.